Salt Taste, Nutrition, and Health (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Salt (NaCl) is a key component of the human diet because it provides the sodium ion (Na+), an essential mineral for our body. Na+ regulates extracellular fluid volume and plays a key role in many physiological processes, such as the generation of nerve impulses. Na+ is lost continuously through the kidneys, intestine, and sweating. Thus, to maintain proper bodily balance, losses have to be balanced with foods containing this cation. The need for salt explains our ability to detect Na+ in foodstuffs: Na+ elicits a specific taste sensation called “salty”, and gustatory sensitivity to this cation is crucial for regulating its intake. Indeed, the widespread use of salt in food products for flavoring and to improve their palatability exploits our sense of taste for Na+. When consumed in excess, however, salt might be detrimental to health because it may determine an increase in blood pressure—a major risk factor for many cardiovascular diseases. Understanding how salt taste works and how it affects food preference and consumption is therefore of paramount importance for improving human nutrition. This book comprises cutting-edge research dealing with salt taste mechanisms relevant for nutrition and health.